2022
DOI: 10.3390/ijms23105553
|View full text |Cite
|
Sign up to set email alerts
|

β-Elemene Attenuates Renal Fibrosis in the Unilateral Ureteral Obstruction Model by Inhibition of STAT3 and Smad3 Signaling via Suppressing MyD88 Expression

Abstract: Renal fibrosis is a chronic pathological process that seriously endangers human health. However, the current therapeutic options for this disease are extremely limited. Previous studies have shown that signaling factors such as JAK2/STAT3, Smad3, and Myd88 play a regulatory role in renal fibrosis, and β-elemene is a plant-derived sesquiterpenoid organic compound that has been shown to have anti-inflammatory, anti-cancer, and immunomodulatory effects. In the present study, the anti-fibrotic effect of β-elemene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…A recent study showed that FBP1 could directly bind to the transactivation domain and the domain containing the nuclear translocation signal of STAT3 to retain STAT3 in the cytoplasm 26 . Our results demonstrated that β‐elemene could reduce the expression level of p‐STAT3 in the nucleus via FBP1, which was consistent with previous studies 39,40 . Subsequent experiments showed that activation of STAT3 could attenuate the effects of β‐elemene on gefitinib‐resistant cells, which indicated that STAT3 was involved in β‐elemene function.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A recent study showed that FBP1 could directly bind to the transactivation domain and the domain containing the nuclear translocation signal of STAT3 to retain STAT3 in the cytoplasm 26 . Our results demonstrated that β‐elemene could reduce the expression level of p‐STAT3 in the nucleus via FBP1, which was consistent with previous studies 39,40 . Subsequent experiments showed that activation of STAT3 could attenuate the effects of β‐elemene on gefitinib‐resistant cells, which indicated that STAT3 was involved in β‐elemene function.…”
Section: Discussionsupporting
confidence: 89%
“… 26 Our results demonstrated that β‐elemene could reduce the expression level of p‐STAT3 in the nucleus via FBP1, which was consistent with previous studies. 39 , 40 Subsequent experiments showed that activation of STAT3 could attenuate the effects of β‐elemene on gefitinib‐resistant cells, which indicated that STAT3 was involved in β‐elemene function. Anti‐apoptosis is a feature of chemoresistance, and β‐elemene exerts anti‐proliferative and anti‐apoptosis effects on tumor growth and multidrug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Before the experiment started, rats were fed adaptively for 1 week and had free access to water and food. Different EEI concentrations were selected based on previously published studies (Ma et al, 2021 ; Sun et al, 2022 ; Wu et al, 2022 ). For 14 days, L-EEI rats received elemene emulsion [20 mg/(kg·d)] intraperitoneally (IP), H-EEI rats received elemene emulsion [40 mg/(kg·d)] IP, and group S rats received the same volume of normal saline IP as H-EEI.…”
Section: Methodsmentioning
confidence: 99%
“…A similar study was performed with β-elemene using the same mouse model of AKI and in vitro rat interstitial fibroblast cells stimulated by TGFβ. Treatment with β-elemene decreased the expression of fibrotic proteins and inhibited SMAD signaling [131]. 12 weeks.…”
Section: Application Of Nutrient Enrichment Strategies For Targeting ...mentioning
confidence: 99%
“…The phytochemicals, such as allicin found in garlic, osthole (a coumarin derivative found in the Umbelliferae and Rutaceae families) [130], and a terpenoid β-elemene found in mint and celery [131], emerge as renoprotective due to their suppression of IL-11 and MAPK/ERK pathways in experimental models [132]. Allicin decreased albuminuria and renal fibrosis, accompanied by reduced expression of TGFβ1 and p-ERK1/2 in a rat model of STZ-induced diabetic nephropathy [132].…”
Section: Application Of Nutrient Enrichment Strategies For Targeting ...mentioning
confidence: 99%